Medical influence: what does success look like? - Diane Wintz; Kelly Wright; Kathryn B. Schaffer (Palliative Care and Social Practice)
Background: Social media influencers have revolutionized information, gaining viewers, retention, and interest with short videos. Medical teams could potentially benefit from this medium for educating patients. Defining success in this endeavor remains unclear. Objective: We are a surgeon-nurse team that sought to promote our messages on social media to gain viewers and interest in our website. Design: An educational podcast focusing on end-of-life discussions was linked to social media platforms, including Instagram and TikTok , to gain views on our website. Methods: Eleven podcast episodes were produced and published over a 3-month period, between November 2023 and January 2024. The podcast episodes were promoted to “similar clients” based on internal algorithms by a podcast streaming service, Spotify . The promotion provided by Spotify and website views were compared to responses evident by other social media posts. Results: After 3 months of publishing podcast episodes on Spotify , with free publicity, our podcast gained 10,400 promotions, 486 listeners, 49 followers, and approximately 1200 random website views. In comparison, the podcast content garnered more than 50,000 video clip views on TikTok and Instagram , after funding these brief video promotions. TikTok and Instagram both charged $20 or more per promotion. Paid promotion opportunities resulted in no website visits or podcast followers. Conclusion: Our own experience with social media promotion was inadequate in generating interest in our content. The authors would encourage other teams to be strategic with paid promotions and to consider engaging a marketing expert to improve the potential for mass interest in content and promotional efficiency. Additionally, based on these findings, the authors would appreciate more transparency in the algorithms behind successful promotions to better understand “what success looks like” for medical messaging.